2003
DOI: 10.1093/carcin/bgh047
|View full text |Cite
|
Sign up to set email alerts
|

Id-1 expression induces androgen-independent prostate cancer cell growth through activation of epidermal growth factor receptor (EGF-R)

Abstract: The failure of prostate cancer treatment is largely due to the development of androgen independence, since the androgen depletion therapy remains the front-line option for this cancer. Previously, we reported that over-expression of the helix-loop-helix protein Id-1 was associated with progression of prostate cancer and ectopic expression of Id-1 induced serum-independent proliferation in prostate cancer cells. In the present study, we investigated if exogenous Id-1 expression in the androgen sensitive LNCaP c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
57
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 21 publications
11
57
1
Order By: Relevance
“…Mobilization of endothelial cell progenitors from the bone marrow is also severely perturbed in Id knockout mice consistent with this hypothesis (10,11). On the other hand, a role for Id1 in modulating tumor epithelial cell behavior is suggested by the fact that overexpression of Id1 in cell lines results in increased invasiveness and metastatic potential of these cells, whereas reduction of high levels of Id1 present endogenously in these lines leads to an inhibition of these properties (12)(13)(14)(15)(16)(17).…”
Section: Introductionsupporting
confidence: 54%
“…Mobilization of endothelial cell progenitors from the bone marrow is also severely perturbed in Id knockout mice consistent with this hypothesis (10,11). On the other hand, a role for Id1 in modulating tumor epithelial cell behavior is suggested by the fact that overexpression of Id1 in cell lines results in increased invasiveness and metastatic potential of these cells, whereas reduction of high levels of Id1 present endogenously in these lines leads to an inhibition of these properties (12)(13)(14)(15)(16)(17).…”
Section: Introductionsupporting
confidence: 54%
“…Reporter expression of the diagnostic system was driven by the cancer-specific expression of Id1, which is a documented indicator of tumor malignancy with no expression found in BPH and normal prostate tissue [11][12][13][14][15][24][25][26][27][28]. The present study used a panel of prostate cancer cells with The dependency of the diagnostic vector on adequate expression of Id1 represents a limitation of the current system for detecting less aggressive cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Id1 gene expression is cancer-specific and has been demonstrated to have increasing levels in human tumors that correlate with increasing Gleason grade and progression [10]. Several studies [11][12][13][14][15] have shown expression of Id1 to be an indicator of malignancy with no expression found in cases of benign prostate hyperplasia (BPH) and normal prostate tissue. The correlation between increased Id1 expression and cancer aggressiveness supports the use of the Id1 promoter for controlling diagnostic reporter function.…”
Section: Introductionmentioning
confidence: 99%
“…We therefore investigated the EGFR expression in Id1 transfected clones. The results showed that EGFR expression was increased significantly indicating that Id1 transfection resulted in increased expression of EGFR [17]. Treatment of DU145 cells with antisense Id1 resulted in downregulation of EGFR indicating the relationship of Id1 and expression of EGFR [17].…”
Section: Involvement Of Id1 In Egfr Upregulationmentioning
confidence: 95%